Rola środków pomocowych z Unii Europejskiej w podnoszeniu atrakcyjności turystycznej gminy Głuchołazy - Puciato, Daniel (The Role of EU Aid Funds in Increasing the Tourist Attractive Ness of the Głuchołazy Commune, 2009)
Tourism is becoming more and more important to Polish national economy, contributing to the domestic product. One of the most significant obstacles preventing it from more dynamic development is the issue of its funding sources. The article presents the role of EU aid funds as a potential instrument that could improve the tourism attractiveness of the Głuchołazy Commune. EU aid funds intended to develop tourism economy of the commune have originated from Phare CBC and Interreg IIIA, and concerned mainly promotion of the commune and development of human resources. To significantly improve the tourism attractiveness of Głuchołazy, more attention should be paid to projects aiming at enhancement of the tourism infrastructure. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 816-824